The Influence of Circuit Training in Improving Technical Skills and Physical Performance of Young Football Players: A Systematic Review - Hardiansyah Hardiansyah; Ahmad Nasrulloh; Sulistiyono Sulistiyono (Physical Education Theory and Methodology)
Objectives. This study aimed to examine the effect of circuit training (CT) on improving technical skills and physical performance for adolescent soccer players, and to provide an understanding of the effective application of CT.